2013
DOI: 10.2319/070212-545.1
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits as a potential predictor of willingness to undergo various orthodontic treatments

Abstract: Objective: To establish an association between patient personality traits and potential willingness to undergo various orthodontic treatments. Materials and Methods: One hundred adolescent individuals aged 12-16 years completed an anonymous electronic questionnaire via Survey Monkey. The 24-item questionnaire contained three major sections: patient demographics, a modified Big Five Inventory (BFI)-10 personality index, and a willingness to undergo treatment assessment. Multiple-variable linear regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…25 Personality, process, and stability are widely recognized as important by researchers in the field of behavioral dentistry, as they can serve to predict patients' perception, treatment modality selection, expectations, compliance, and satisfaction with treatment outcome. [26][27][28][29] Recent research suggests that self-perceived malocclusion is not a predictor of personality traits, meaning that there is an outside possibility that malocclusion, that is, the perception of malocclusion, is an external factor that might modify onè s personality traits. However, age and sex have some effect on personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…25 Personality, process, and stability are widely recognized as important by researchers in the field of behavioral dentistry, as they can serve to predict patients' perception, treatment modality selection, expectations, compliance, and satisfaction with treatment outcome. [26][27][28][29] Recent research suggests that self-perceived malocclusion is not a predictor of personality traits, meaning that there is an outside possibility that malocclusion, that is, the perception of malocclusion, is an external factor that might modify onè s personality traits. However, age and sex have some effect on personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Hansen et al 10 showed that personality traits had a modest but significant correlation to potential willingness to undergo various orthodontic treatments. They reported that agreeableness proved to be the trait most often associated with willingness to undergo different orthodontic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition; Cooper-Kazaz et al [19] reported that personality traits and psychological features have signi cant impact on adjustability and recovery during xed buccal orthodontic treatment in adult patients; they used Brief Symptom Inventory to assess personality trait. Hansen et al [20] and Singh et al [21] observed that personality traits are useful in predicting a patient's potential willingness and cooperation during xed orthodontic treatments. The ndings of the current study performed on a different population with different psychological and cultural background have con rmed the results yielded by aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%